Trace Elements' Contamination of Pediatric Parenteral Nutrition Solutions in Canada: A Cause for Concern. Issue 2 (27th April 2020) - Srikrishnaraj, Arjuna; Chambers, Kathryn; South, Courtney; Arppe Robertson, Megan; Vresk, Laura; Tedesco‐Bruce, Anna; Haliburton, Beth; Yanchis, Dianna; Belza, Christina; Zietsma, Jordan; Benec, Joanna; Carricato, Megan; et al.
Abstract: Background: Trace elements' (TEs) contamination of parenteral nutrition (PN) solutions is an ongoing concern. The aims of this study were 1) to measure actual TE concentrations in PN admixtures compared with ordered concentrations and 2) compare TE intake with current recommendations. Methods: PN admixtures from discarded bags were collected from patients receiving home PN and on inpatient wards. Samples were collected from 72 patients (39 inpatients, 33 receiving home PN). Age, percentage energy intake from PN, and PN orders were collected from patients' charts. PN samples were analyzed for TEs, including chromium (Cr) and manganese (Mn), and concentration measurements compared with ordered concentrations and current recommendations. Results: Measured Cr and Mn concentrations were higher than ordered concentrations: 5.3 ± 1.7 vs 2.8 ± 1.5 µg/L; P < 0.0001 and 11.9 ± 5.9 vs 0.00 µg/L; P < 0.0001, respectively. Chromium contamination alone accounted for over 100% of current recommendations for patients 0–12 months and between 63% and 92% for children >1 year. Contamination of Mn provided all the measured Mn in PN admixtures, since Mn is excluded from PN orders at our institution. Between 70% and 120% of current Mn recommendations were met from contamination. Conclusions: Cr should be excluded from PN admixtures for children 0–12 months and only one‐fourth the current recommendation should be added for pediatric patients >1 year. Manganese should also be excluded from PN admixture for pediatric patients but plasms monitoring 2–3 times per year is recommended for those on long‐term PN.